TWO KNOWN AND ONE NEW SPECIES OF NEMATA FROM MANIPUR - MOHILAL, N.; ANANDI, Y.; DHANACHAND, CH. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
Survey of parasitic nematodes in different areas of Manipur revealed the occurrence of one known species of Paratylenchus, another known and one new species of Hemicriconemoides. Paratylenchus longicaudatus Raski, 1975 is a new record in India.